The Role of The Nation and State Youth in the Era of Adaptation of New Habits of the Covid-19 Pandemic - Kusumawati, Karisna; Pandin, Moses (Universitas Pendidikan Ganesha, 2024)
Since 2020, Indonesia has treated COVID-19 as a national emergency, prompting a rapid shift to online learning and daily activities. This literature review examines the role of youth (adolescents, university students, and young adults) during the “new normal” adaptation period and explores factors underlying uneven awareness. A qualitative, descriptive review of articles from Scopus and university journals was conducted, complemented by social-media monitoring; an exploratory online questionnaire yielded 55 responses. The findings reveal variability in COVID-19 knowledge among some youth, mixed risk perceptions, and inconsistent compliance with health protocols, alongside strong potential for youth leadership as digital communicators, peer educators, and community volunteers. Youth engagement as agents of change included promoting accurate information, encouraging protocol adherence, and articulating bottom-up critiques of policies perceived as inequitable for vulnerable groups. We conclude that empowering youth is pivotal to reducing transmission while sustaining civic values during crisis adaptation. Practical implications include targeted health-literacy campaigns on social platforms, peer-led outreach in schools and communities, and partnerships among youth organizations, educators, and health authorities to model and reinforce protective behaviors. Limitations include the small, non-representative survey (n=55); future research should employ larger, probabilistic samples and mixed methods to evaluate which youth-centered interventions most effectively build awareness, responsibility, and resilience during and after public-health emergencies.